1997
DOI: 10.1103/physrevb.56.8912
|View full text |Cite
|
Sign up to set email alerts
|

Eu-Eu exchange interaction and Eu distribution inPb1xEuxTefrom magnetizatio

Abstract: The magnetization of Pb1−xEuxTe samples with x = 1.9, 2.6 and 6.0% was measured at 20 mK in fields up to 50 kOe, and at 0.6 K in fields up to 180 kOe. The 20 mK data show the magnetization steps (MSTs) arising from pairs and from triplets. The pair MSTs are used to obtain the dominant Eu-Eu antiferromagnetic exchange constant, J/kB = −0.264 ± 0.018 K. The exchange constant for triplets is the same. Comparison of the magnetization curves with theoretical simulations indicates that the Eu ions are not randomly d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
(44 reference statements)
3
12
0
Order By: Relevance
“…This betters the agreement with the experimental results [4]. It may be noted that a new experiment [23] suggests that the magnetic ions are not randomly distributed in the host matrix. But we believe the problem is not yet resolved.…”
Section: Resultssupporting
confidence: 74%
“…This betters the agreement with the experimental results [4]. It may be noted that a new experiment [23] suggests that the magnetic ions are not randomly distributed in the host matrix. But we believe the problem is not yet resolved.…”
Section: Resultssupporting
confidence: 74%
“…These results have been well explained by the model of superexchange interaction between the nearest neighbors (NN) via an anion. Bindilatti et al and ter Haar et al investigated the high-field magnetization in A IV B VI SMSs and found exchange constant values similar to ours [10,9,11]. A review of magnetic susceptibility and magnetization studies, including exchange among more distant magnetic ions, is given in [12].…”
Section: Introductionsupporting
confidence: 54%
“…Magnetization steps in rare‐earth‐doped IV–VI DMS were shown in magnetization measurements at 20 mK. [ 42–48 ] The influence of clusters bigger than pairs was taken into account and discussed in detail. [ 49 ]…”
Section: Magnetic Susceptibility and Magnetizationmentioning
confidence: 99%